The system approach to innovative development of regional foodstuff market in conditions of crisis - Gafarova, Elena (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
Efficient control of the consumer foodstuff market can be considered a key direction of economic development of Irkutsk region. This market is strategically important for forming human capital of the region, as food is a basis for preservation and maintenance of population’s health.The economic crisis has been negatively reflected in functioning of the market of foodstuff that is caused by the factors having both internal and external character. Increasing the cost of some kinds of food has negatively affected consumers’ demands, as the incomes of the population in the conditions of crisis are decreasing. The structure of production and sells of foodstuff has changed. While retail prices are growing, the wholesale ones (for the peasants) are decreasing. The lack of coordinated communication between manufacturers and consumers interfered with the process of replacing imported goods with domestic products. Due to long procedures of registration for credits and insufficiency or absence of pledge, the possibilities of small businesses were limited in subsidizing programs. In the conditions of economic crisis, the primary task of the enterprises of food-processing industry should be aspiring to innovative development as well as decreasing the expenses for manufacturing and selling competitive products.